Hollow Iridium-Based Catalysts for the Oxygen Evolution Reaction in Proton Exchange Membrane Water Electrolyzers. (24th August 2017) - Peron, Jennifer; Faustini, Marco; Giraud, Marion; Rozière, Jacques; Jones, Deborah J.; Boissière, Cédric; Tard, Cédric
Abstract : Hollow IrO2 microspheres were synthesized directly from aqueous solution using hydrated IrCl3 in presence of a porogen. This step was followed by thermal treatment in air at different temperatures to achieve the oxidation of the porogen and crystallization of IrO2 . The temperature of this treatment was found to be crucial to finely tune the structural, morphological and electronic features of the synthesized materials, which has a strong impact on their electrochemical performance.